Applying a Value Stream Mapping (VSM) to improve supply chain performance of agricultural products: A case of Thai exported canned lychee - Roengchai Tansuchat (2018)
© 2017 Serials Publications Pvt. Ltd. A value chain concept has been applied to business to improve supply chain performance of various product. However, it was found that there is a few research in fruit value chain improvement. This paper, we applied a value stream mapping technique to improve supply chain performance of an agricultural product, lychee. This study aimed to analyze activities and linkages in the Thai canned lychee supply chain and to identify problems and obstacles including how to improve its efficiency and effectiveness. Data were collected from a survey of key players in the supply chain including farmers, local lychee collectors, agricultural cooperatives, canned lychee factories, exporters and importers. In addition, this research has also applied the value stream mapping (VSM) to classify the supply chain activities into three main activities include value added (VA), non- value added (NAV) and necessary non-value added activities (NNVA). After analyze value stream mapping in the current state this research found that NVA can be eliminated or reduced such as activities of intermediaries and some production process. The new VSM can reduce the supply chain activities significantly. This paper provides insights into a global fruit value chain with empirical evidence of improvement.